Cyborgs in Latin America - Brown, J. Andrew (Springer Nature, 2010)
Cyborgs in Latin America explores the ways cultural expression in Latin America has grappled with the changing relationships between technology and human identity. The book takes a literary and cultural studies approach in examining narrative, film and advertising campaigns from Argentina, Bolivia, Chile, Mexico and Uruguay by such artists as Ricardo Piglia, Edmundo Paz Soldán, Carmen Boullosa and Alberto Fuguet among others. Using and criticizing theoretical models developed by Katherine Hayles, Donna Haraway, Gilles Deleuze and Michel Foucault, the book will appeal to specialists and students of Latin American Studies; Posthuman Theory; and Literature, Science and Technology Studies.